Fertility in beef cattle synchronized with prostaglandin, gonadotropin and progestogens - Walker, Ryon Shaw, author; Zalesky, Douglas D., advisor; Engle, Terry E., committee member; Mortimer, Robert G., committee member; Whittier, Jack C., committee member; Burns, Patrick D., committee member (Colorado State University. Libraries, 2004)
Three objectives were studied to evaluate maximizing fertility by introducing dietary fat supplementation, exogenous hCG injections and synchronization protocols into management programs. The first objective (Chapter 2) were to determine if supplementing 0.96 kg of whole safflower seeds for an average of 55 d beginning 35 d prior to AI with an hCG injection post AI would increase fertility in beef heifers. Nulliparous crossbred beef heifers from separate breeding seasons in the same year (early breeding heifers [EBH], n=48; late breeding heifers [LBH], n=48) were stratified by BW, BCS and age within breeding season and assigned to treatments in a 2 x 2 factorial arrangement with factors being a control diet (CON) consisting of mixed alfalfa/grass hay and oat grain or a safflower seed diet (SAFF) consisting of the control diet plus safflower seed high in oleic (69.9%) acid with hCG or saline injections given 5 d post AI. Diets were formulated to be isocaloric and isonitrogenous for both groups. Heifers were fed their respective diets beginning 35 d prior to AI and continued 11 to 28 d post AI. All heifers were synchronized with the 7-11 MGA Select Synch protocol. Blood samples were collected from all heifers 5 consecutive days beginning 4 d after AI and analyzed for progesterone concentrations. On day -35, -20 and 0 prior to AI, blood samples were collected and analyzed for fatty acid composition in all heifers. First-service conception rates were higher (P < 0.05) for EBH (79.5%) vs LBH (51.4%) heifers; however, there were no diet x treatment interaction on fertility (P > 0.10), therefore data from both breeding seasons were pooled. Conception rates were similar (P > 0.10) for heifers in the CON vs SAFF and hCG vs saline groups. Serum progesterone levels were similar (P > 0.10) for CON and SAFF heifers; however, progesterone concentrations increased over time (P < 0.05) for hCG vs saline injected heifers. Serum stearic acid increased and serum linolenic acid decreased (P < 0.01) for both diet groups over time. Serum oleic acid increased (P < 0.01) over time for heifers in the SAFF vs CON group. Feeding 0.96 kg of whole safflower seed for an average of 55 d beginning 35 d prior to AI with hCG given 5 d post AI did not improve fertility; however, hCG increased serum progesterone levels. The second objectives (Chapter 3) were to evaluate optimal timing for timed AI (TAI) using a Co-Synch protocol with or without GnRH at TAI and calf removal. Multiparous Composite and Hereford suckling beef cows (n=226) were synchronized for AI from two separate calving seasons in the same year. Early (ECC) and late calving cows (LCC) were randomly assigned to one of four treatment groups for a 2 x 2 factoral arrangement. All cows were injected with 100 pg of GnRH on day 0, followed by 25 mg of PGF2α (PG) on day 7. All calves were removed at time of PG and returned to nurse at TAI. Half of the cows were inseminated 48 h post PG with (48-TAI-G) or without (48- TAI) GnRH and the other half were inseminated 72 h post PG with (72-TAI-G) or without (72-TAI) GnRH. Pregnancy rates were not affected (P > 0.10) by calving season; therefore data from both ECC and LCC were combined. Body condition and PPI did not influence fertility (P > 0.10); however pregnancy rates increased (P < 0.01) 20.5% for cows inseminated at 72 vs 48 h, and 15.9% for cows receiving GnRH vs no GnRH (P < 0.05) at TAI. Pregnancy rates varied (P < 0.05) for cows inseminated to sires A (33.3%) and sires B and C (51.8 and 54.3%). We concluded that fertility levels may have been compromised from one of the three sires used; however, delaying TAI 72 h after PG with GnRH improved timed AI pregnancy rates. The third objective (Chapter 4) were to determine if a second injection of GnRH at timed AI (TAI) increases the percentage of induced ovulations and improves pregnancy rates in beef heifers synchronized with the CO-Synch plus CIDR protocol. Nulliparous crossbred beef heifers (n = 375, BW = 362.7 kg, body condition score, BCS = 5.6) from three locations (Colorado [CO], Wyoming [WY] and South Dakota [SD]) were stratified by BW within BCS and randomly allotted to one of two treatments. All heifers received 100 μg of GnRH with a CEDR insert on day 0, followed by CIDR removal and 25 mg of PGF2α (PG) on day 7. At 54 hours post PG, heifers in the control (CON) and treatment (TRMT) groups were mass mated and heifers in the TRMT group were given a second injection of GnRH at that time. Blood samples were collected in heifers at d -10 and 0 to determine cyclicity status at CO and WY. Ultrasonography was used to classify follicle diameter at TAI and determine percentage of heifers ovulating 40 h after TAI at both CO and WY locations. Heifers at the SD location were assigned to a time group (1 to 6; 1 = 54 h and 6 = 59 h) based on the hour inseminated beginning 54 h post PG. Cyclicity rates were higher (P < 0.01) for heifers at CO (97.4 %) vs WY (46.4 %). Pregnancy rates were similar (P > 0.10) between treatment groups and for cycling and non-cycling heifers at CO and WY; however, pregnancy rates were higher (P < 0.05) for heifers in the TRMT (54.2 %) vs CON group (40.4 %) at SD. Body weight did not affect pregnancy rates for either treatment group across all locations (P > 0.10); however, pregnancy rates tended to decrease (P = 0.08) for heifers with body weights greater than 409.1 kg (39 %) vs heifers with body weights less than 409.1 kg (53.2 %) at SD. The percentage of heifers ovulating were similar (P > 0.10) between CO and WY and ovulation rates tended to be higher (P = 0.10) for heifers in the TRMT (81.3 and 73.9 %) vs CON (62.5 and 66.7 %) groups at CO and WY. Pregnancy rates were higher (P < 0.05) at CO and WY for heifers ovulating by 40 h after TAI (50 and 61.8 %) vs heifers that had not ovulated at that time (16.7 and 16.7 %). Effect of time group, over time, on pregnancy rates were not seen (P > 0.05) for SD heifers. We conclude that synchronizing beef heifers with a modified CO-Synch plus CIDR protocol induces ovulation in cycling and non-cycling heifers and produces acceptable pregnancy rates at 54 h TAI. The value of incorporating a second injection of GnRH at timed AI remains questionable.
Keywords: animal diseases; anatomy and physiology; animals